Fiscal policy in Argentina, Brazil, and Mexico and the 2030 Agenda for Sustainable Development - Bendreff Desilus (Levy Economics Institute of Bard College, 2020)
Fiscal policy is useful as a government instrument for supporting the economy, contributing to an increase in employment, and reducing inequality through more egalitarian income distribution. Over the past 30 years, developing countries have failed to increase their real wages due to the lack of domestic value-added in the era of globalization, where global supply chains are the driving factor for attracting foreign direct investment. Under such circumstances, the role of fiscal policy has become an important factor in creating the necessary conditions for boosting the economy. With the end of commodity-export-led growth, Mexico experienced a moderate reduction of 5 percent in poverty between 2014 and 2018 due to the structural adjustment of social policies and its economic and trade relationship with the United States; during the same period there has been no change in poverty in Argentina, and Brazil has suffered a rise in poverty. Following the global financial crisis, greater attention has been paid to fiscal policy in developed and developing countries-specifically Argentina, Brazil, and Mexico (ABM)-in order to attain macroeconomic stability. One of the consequences of the financial crisis is rising income inequality and its negative effects on economic growth. Over the past decade, fiscal policy has been adopted for the economic recovery. However, the recovery has been accompanied by a decrease in real wages of the middle class. The purpose of the present research is to critically examine the results of fiscal policy in ABM and the United Nations' 2030 Agenda for Sustainable Development.
Keywords: E24; D63; J21; Q56; I38; 330; Wages; Inequality; Productivity; Full Employment; Sustainability; Government Policy